মুক্তিযুদ্ধের মানুষ মুক্তিযুদ্ধের স্বপ্ন - রহমান, আতিউর 1951- (ঢাকা : সাহিত্য প্রকাশ, 1997)
Articles chiefly on the 1971 liberation movement of Bangladesh.
Includes bibliographical references and index.
In Bengali; includes passages in English.
Keywords: Bangladesh -- History -- Revolution, 1971.